Learning Strategies at SMP Muhammadiyah 4 Porong During Pandemic Covid 19 - Mochammad Syahrul Mustofa (International Consortium of Education and Culture Research Studies, 2021)
This study aims to examine the history and learning strategies during the Covid-19 pandemic from SMP Muhammadiyah 4 Porong. In the research process this time using descriptive qualitative research methods. Data collection techniques in this study were through data with interviews, observations, and photo documentation during the research process. Based on the results of this study, the history of the establishment of SMP Muhammadiyah 4 Porong in the 1960s, but after the Lapindo Mud tragedy in May 2006 which resulted in a decrease in population movement because their houses were already submerged in mud and the process was the relocation of Muhammadiyah College from Mindi Village to Lajuk Village, Porong District. in 2016. Other research results regarding the learning strategy of SMP Muhammadiyah 4 Porong during the Covid-19 pandemic, namely conducting digital learning using online application media devices until January 2021. The school also improvised to change the online and offline education system in every 7th, 8th grade, and 9 by complying with health protocols; so that learning activities can run well. The conclusion of this research is the journey of SMP Muhammadiyah 4 Porong which continues to rise from the adversity of the 2006 Lapindo Mud tragedy and struggles to overcome learning barriers due to the Covid-19 pandemic through digital learning, namely the Edmodo application